Suitable Fuel Terminal Pertamina Pulau Sambu Business and Marketing Strategy Facing the Impact of Permanent Establishment Taxation Policy in Oil & Gas Storage Terminal Business - Achmad Ariansyah (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2026)
Singapore's declaration to participate as a pioneering country in the energy shift and become the first Southeast Asian country to implement a carbon pricing scheme on January 1, 2019, by imposing a carbon tax has led several major players in this business to divest their terminals or refineries in the Singapore area or shift their businesses to green energy, such as Shell and Advario. This phenomenon, however, does not eliminate dependence on fossil fuels. Therefore, demand for storage tank rental and bunkering services will remain and continue to increase, especially in the Strait of Malacca. This creates an opportunity for Pulau Sambu Fuel Terminal to become an alternative storage location, strengthened by its strategic location in the Singapore Strait and its currently unutilized condition. Regulatory challenges related to tax regulations directly impact the competitiveness of Pulau Sambu, which becomes less attractive when compared to existing terminals in Singapore and Malaysia. This research uses a mixed-methods approach, combining qualitative methods as well as analysis of secondary data. This research is structured using several analytical frameworks such as PESTLE analysis, Porter's Five Forces, VRIO, and the SWOT-TOWS matrix to obtain a comprehensive picture of internal and external conditions as part of an effort to obtain precise business and marketing strategies. Finally, this research gives a clear visual across both academic literature and industrial practices. For practitioners, the findings offer a blueprint for a phased business model, uniting investment strategies along with government engagement.